Proposta de modelo para gerenciamento de processos: estudo de caso - Schefer, Solange de Fatima (2009)
The modern approach of the agribusiness considers all companies that produce, process, and distribute farming products. Worried about performance, as well as waste and grain loss, the companies have been professionalized, implanting technologies, creating, planning and controlling its management. On the other hand the requirements in changing the agro-industrial process have affected its technological necessities, operation and performance. The objective of this study was to develop a model for process management, being considering the characteristics of the agribusiness, and applying it to the management of activities present in the handling and storage of grains. The research is based on recognized methodologies for the management of processes, suggesting a new model. This model has the objective to control the processes through the standardization and to seek constant improvement, being that the chosen activities are inserted in the context of the agribusiness. The research refers to a case study and is characterized as a descriptive, qualitative exploratory research. The contribution of the research is considered important, getting to know the processes, people involved and technologies, to identify the key processes and to propose a model for managing the processes. The suggested model is being applied in a cooperative of storage, improvement and commercialization of grains, but it may be applied to any type of organization, after going through the necessary adaptations and testing. The research also suggested new indicators for process control, creating the expectation that the organization, through these will be able to have more effective data control.